Academic Supervision and Principal Managerial Competence as Determinants of Teacher Performance: Evidence from SMA Negeri 1 Soreang - Ryan Mukhtari Fadli; Salma Aulia Andanie Puteri; Nur Aedi; Suryadi Suryadi (Journal of Business, Social and Technology, 2026)
Background: Teacher performance is closely linked to instructional quality, and school leadership may shape it through academic supervision and managerial practice. Objective: This study examines whether academic supervision and the principal’s managerial competence are associated with teacher performance at SMA Negeri 1 Soreang. Methods: A quantitative correlational survey collected 1–4 Likert-scale responses from 19 purposively selected teachers. Descriptive statistics, assumption tests, correlations, and simple and multiple regression analyses were conducted using IBM SPSS Statistics 29. Results: Academic supervision explained 76.4% of the variance in teacher performance, while managerial competence explained 72.2%. Their joint model was significant (F = 25.970, p < .05) and accounted for 76.4% of the variance. Because the two predictors were highly correlated, partial findings are interpreted cautiously. Conclusion: Teachers appear to experience supervision and managerial leadership as interconnected features of principal leadership. Schools should strengthen classroom-focused supervision, feedback, and managerial support as complementary improvement practices.